BN‐Anthracene for High‐Mobility Organic Optoelectronic Materials through Periphery Engineering. Issue 24 (12th April 2022) - Li, Wanhui; Du, Cheng‐Zhuo; Chen, Xing‐Yu; Fu, Lin; Gao, Rong‐Rong; Yao, Ze‐Fan; Wang, Jie‐Yu; Hu, Wenping; Pei, Jian; Wang, Xiao‐Ye
Abstract: Despite the remarkable synthetic accomplishments in creating diverse polycyclic aromatic hydrocarbons with B−N bonds (BN‐PAHs), their optoelectronic applications have been less exploited. Herein, we report the achievement of high‐mobility organic semiconductors based on existing BN‐PAHs through a "periphery engineering" strategy. Tetraphenyl‐ and diphenyl‐substituted BN‐anthracenes (TPBNA and DPBNA, respectively) are designed and synthesized. DPBNA exhibits the highest hole mobility of 1.3 cm 2  V −1  s −1 in organic field‐effect transistors, significantly outperforming TPBNA and all the reported BN‐PAHs. Remarkably, this is the first BN‐PAH with mobility over 1 cm 2  V −1  s −1, which is a benchmark value for practical applications as compared with amorphous silicon. Furthermore, high‐performance phototransistors based on DPBNA are also demonstrated, implying the high potential of BN‐PAHs for optoelectronic applications when the "periphery engineering" strategy is implemented. Abstract : High‐mobility organic semiconductors based on classical BN‐embedded polycyclic aromatic hydrocarbons (BN‐PAHs) have been achieved through a "periphery engineering" strategy. Remarkably, diphenyl‐substituted BN‐anthracene (DPBNA), with a highest hole mobility of 1.3 cm 2  V −1  s −1 in organic field‐effect transistors and excellent performance in phototransistors, is the first BN‐PAH that outperforms amorphous silicon.